KONTROL SUHU PADA GENERATOR SET DENGAN MENGGUNAKAN MIKROKONTROLER - Axel Dewo Augustama; Sujono Sujono (MAESTRO, 2020)
Generator set (Genset) is a device that can convert mechanical energy into electrical energy. In a generator et that operates to supply electricity to a load, the amount of electric current that occurs will cause an increase in heating that occurs in the engine and if not maintaeined it may cause overheating. This paper discusses the automatic generator set temperature control system to prevent overheating conditions on the generator set while operating. The control system used is the ESP-32 microcontroller with algorithm Proporsional Integral and Derivative (PID). The DS18B20 temperature sensor is used to detect the actual temperature on the generator set. As an actuator in regulating the tempreture of generator set, a 12 Volt dc fan is used. The way the temperature control works starts at the ds18b20 temperature sensor detects the temperature on the data is processed with the PID algorithm by the ESP-32 microcontoller to produce a PWM value which will be fed to the 12 Volt dc fan as an actuator. Based on tests that have been done by giving variables to Kp, Ki, Kd in order to produce a stable system response, it is obtained with the variable value Kp=2, Ki=5, Kd=1 set point 57 oC, the value of the rise time is 35 seconds, overshoot 2.19 oC, settling time 109 seconds and steady state error of 0.44 oC. In another test at the setpoint of 70 oC with variable values Kp=3, Ki=2, Kd=2, the value of rise time is 47 seconds, overhoot 2.06 oC, settling time 114 seconds, steady state error 2.31 oC.